Temperatura de almacenamiento y cantidad de ARN extraído de plasma maternos - Ayala Ramírez, Paola Andrea; Pontificia Universidad Javeriana (2013)
The discovery of nucleic acids in maternal plasma unlocked new possibilities for noninvasive prenatal diagnosis. However, the factors affecting the concentration of fetal RNA in maternal plasma samples are unspecified. Here we studied the effect of storage time (15 to 30 days) and temperature (4°C, -20°C and ambient) and of the presence of Trizol on the concentration of RNA in plasma samples taken from pregnant women before their 20th week. Thirty-three RNA samples were extracted from plasma and analyzed by spectrophotometry. The amount of RNA was statistically lower in samples stored at -20°C whereas storage time and the presence or absence of Trizol did not affect RNA level. Temperature affected the concentration of RNA, rather than time and the addition of Trizol. In conclusion, temperature is akey factor in the extraction of RNA, and the freeze-thaw process most likely affects RNA concentrations negatively.